2019
DOI: 10.1021/acsanm.9b00430
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4Nanoparticles Dispersed on Douglas Fir Biochar for Phosphate Sorption

Abstract: Surface area, particle aggregation, pressure drop in columns, nanotoxicity, and commercialization difficulties limit the use of nanoparticle adsorbents. Magnetic primary nano-Fe3O4 particles (∼16.7 nm diameter) were dispersed on high-surface-area (695 m2/g) Douglas fir biochar (MBC). A cheap, commercial fast pyrolysis biochar, a syngas byproduct, was modified by chemical coprecipitation of Fe3O4 from Fe3+/Fe2+ aqueous NaOH, served as a matrix, aiding magnetite nanoparticle dispersion and reducing the extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 64 publications
2
46
1
Order By: Relevance
“…The fixed-bed parameters including total time ( t x ), mass flow rate ( F m ), time required for PAZ movement ( t δ ), depth (δ), time needed for initial PAZ formation ( t f ), amount of fluoride adsorb ( M s ), column fractional capacity ( f ), percent saturation, empty-bed-contact-time (time required for influent to be in contact with biochar bed), and biochar usage rate were calculated using eqs 4–10. 46,80−84 …”
Section: Methodsmentioning
confidence: 99%
“…The fixed-bed parameters including total time ( t x ), mass flow rate ( F m ), time required for PAZ movement ( t δ ), depth (δ), time needed for initial PAZ formation ( t f ), amount of fluoride adsorb ( M s ), column fractional capacity ( f ), percent saturation, empty-bed-contact-time (time required for influent to be in contact with biochar bed), and biochar usage rate were calculated using eqs 4–10. 46,80−84 …”
Section: Methodsmentioning
confidence: 99%
“…Results of an ATR-FTIR analysis showed that calcium carbonate was a main adsorption site for phosphorus of Mallee biochar, which represented a 16% increase in phosphorus adsorption and more than 50% of which were accessible to plant uptake in Mallee biochar (5% w/w) conditioned soils [108]. Surface activation by chemicals, such as metal salts, alkali, and nano-particles, significantly enhanced the phosphorus adsorption capacity of biochar [105,106,[110][111][112]. Phosphate adsorption capacity increased from 2.1% of untreated to 70.3% of magnesium treated Oak biochar [106].…”
Section: Adsorption Of Phosphorus Species 231 Inorganic Phosphorusmentioning
confidence: 99%
“…Results on phosphorus removal from secondary wastewater effluents by biochar loaded with colloidal and nano-sized aluminum oxyhydroxide crystalline flakes showed that, in less than 8 h, 8.3 g of phosphorus was adsorbed per kg of engineered biochar in a fixed-bed column [112]. Loading biochar with magnetic nano-particles increased phosphate adsorption capacity by 20-fold compared to that of nano-magnetite [110]. Furthermore, the pyrolysis of poultry litter biomass with phosphate, phosphoric acid, and magnesium oxide strongly decreased dissolved phosphorus concentrations due to the strong adsorption and slow-release of phosphate in soils, which facilitated the phosphorus utilization rate [113].…”
Section: Adsorption Of Phosphorus Species 231 Inorganic Phosphorusmentioning
confidence: 99%
“…Similarly, the pH PZC of MgO is 12.4, and the anionic dye adsorption is driven by electrostatic forces. The pH PZC of TiO 2 is around neutral values (6-6.8), which is not so much different from those of iron oxides; the PZC values measured for FeO, Fe 3 O 4 , and Fe 2 O 3 were around 6.1-6.5 [28,29]. The pH PZC of TiO 2 and iron oxides is in the neutral range, making them efficient adsorbents for both cationic and anionic dyes in a wide range of pH mediums.…”
Section: Adsorptive Removal By Inorganic Absorbents Incorporated Intomentioning
confidence: 71%